If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = 6(x + -2) + -4(x + -3) Reorder the terms: 7 + 5x = 6(x + -2) + -4(x + -3) Reorder the terms: 7 + 5x = 6(-2 + x) + -4(x + -3) 7 + 5x = (-2 * 6 + x * 6) + -4(x + -3) 7 + 5x = (-12 + 6x) + -4(x + -3) Reorder the terms: 7 + 5x = -12 + 6x + -4(-3 + x) 7 + 5x = -12 + 6x + (-3 * -4 + x * -4) 7 + 5x = -12 + 6x + (12 + -4x) Reorder the terms: 7 + 5x = -12 + 12 + 6x + -4x Combine like terms: -12 + 12 = 0 7 + 5x = 0 + 6x + -4x 7 + 5x = 6x + -4x Combine like terms: 6x + -4x = 2x 7 + 5x = 2x Solving 7 + 5x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 7 + 5x + -2x = 2x + -2x Combine like terms: 5x + -2x = 3x 7 + 3x = 2x + -2x Combine like terms: 2x + -2x = 0 7 + 3x = 0 Add '-7' to each side of the equation. 7 + -7 + 3x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = 0 + -7 3x = 0 + -7 Combine like terms: 0 + -7 = -7 3x = -7 Divide each side by '3'. x = -2.333333333 Simplifying x = -2.333333333
| -60/-12 | | -7x^2-7x+9=0 | | 3y-9+y+27=5y+20-3y | | 3x^4-4x^3-30x^2-36x+112=0 | | 3(3z-1)-3(2z)=5 | | k=8+28 | | 45*5/9=c | | (-4x^3+2x^2-2x+8)+(8x^3+8x^2-7x-10)= | | 14x^3=13x^2 | | 10-24=s | | 7(y+4)=-8y-17 | | f(x)=5x^4-3x^2 | | X^2(14x-13)=0 | | 12d^2-31d+20=0 | | 3m-6=2m-12 | | (f/g)(x)= | | 0.0089x-0.32+0001(5-x)=0.231 | | 4sin^2x-3sinx=0 | | 5x^3-36x^2-43x+10=0 | | 5=v/4-10 | | x^2+6x+9=81 | | 33x^6-64x^3+15x^4=0 | | 14p-8=28+20p | | x(6.25)=68.75 | | t/6-4=16 | | 6.24x+56.16=112.32 | | 14x^3-13x^2=0 | | 4/3y-3/4x=12 | | 3X^3+8x^2+2x-28=0 | | 3(10x+5y)+5=65 | | 9y-1=4-25 | | 4z/7-6=7 |